1986
DOI: 10.1093/jac/18.supplement_b.103
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity monitoring of herpes simplex virus isolates from patients receiving acyclovir

Abstract: A simple plaque-reduction assay was used to determine the acyclovir sensitivity of herpes simplex virus isolates taken from patients enrolled int he acyclovir clinical trial programme. The resultant data revealed no reduction in acyclovir sensitivity in virus from those patients, with a normal immune status, receiving topical, oral or intravenous acyclovir for the treatment of acute disease episodes. In the treatment or prophylaxis of chronic herpes infections in immunocompromised patients reductions in sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Characterization of laboratory-generated resistant mutants indicates that resistance arises as a result of loss or alteration of thymidine kinase (TK) activity or alteration in the virus DNA polymerase (4,15,18,23). Virus isolates recovered from clinical trials of ACV in immunocompetent patients have been monitored and have shown little evidence of alteration in their susceptibility to ACV (2,8). However, there have been a small number of reports of the isolation of virus with reduced susceptibility, particularly from bone marrow transplant patients and leukemic patients undergoing induction chemotherapy (2,3,8,9,16,24,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of laboratory-generated resistant mutants indicates that resistance arises as a result of loss or alteration of thymidine kinase (TK) activity or alteration in the virus DNA polymerase (4,15,18,23). Virus isolates recovered from clinical trials of ACV in immunocompetent patients have been monitored and have shown little evidence of alteration in their susceptibility to ACV (2,8). However, there have been a small number of reports of the isolation of virus with reduced susceptibility, particularly from bone marrow transplant patients and leukemic patients undergoing induction chemotherapy (2,3,8,9,16,24,30).…”
mentioning
confidence: 99%
“…Virus isolates recovered from clinical trials of ACV in immunocompetent patients have been monitored and have shown little evidence of alteration in their susceptibility to ACV (2,8). However, there have been a small number of reports of the isolation of virus with reduced susceptibility, particularly from bone marrow transplant patients and leukemic patients undergoing induction chemotherapy (2,3,8,9,16,24,30).…”
mentioning
confidence: 99%
“…Virus purified from isolate l was consistently sensitive to ACV (0.7 to 3.3 gM)although they were in the upper end of the range previously observed for type 1 viruses (Collins & Oliver, 1986 Viruses purified from isolate 8 were 10 to 30-fold less sensitive to ACV than those from isolate 1 and two-to fourfold less sensitive to PAA, although there was slight variation these values compared well with the uncloned isolate.…”
Section: Plaque-purified Variantsmentioning
confidence: 57%
“…Despite the chronic nature of herpesvirus infections in these patients acyclovir (ACV) treatment has been shown to be effective clinically (Mitchell et al, 1981 ;Wade et al, 1982;Meyers et al, 1982;Whitley et al, 1984;Shepp et al, 1985). However, the prolonged treatment required for these indolent infections may result in the selection of resistant virus variants (Barry et aL, 1985;Collins & Oliver, 1986;Collins, 1988). The frequency of such occurrences cannot be determined, since the sensitivity of virus isolates has only been assessed following poor clinical response, and even this did not always correlate with the appearance of a resistant phenotype (Barry et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The effect that prolonged exposure to ACV could have in selecting resistant HSV isolates in patients with a lesser degree of immunosuppression (such as transplant recipients) is not well defined. Although a few studies have examined HSV susceptibilities in BMT patients receiving ACV prophylaxis (5,17), systematic monitoring of ACV susceptibilities has not been done in SOT patients who excrete HSV during or after antiviral prophylaxis. In a large prophylactic trial of ACV for CMV infection conducted at our institution, 2 (3.8%) of 53 kidney transplant recipients randomized to receive ACV developed mucocutaneous HSV infections (2), but the ACV susceptibilities of those HSV isolates were not determined.…”
mentioning
confidence: 99%